IMPLEMENTING PADLET APPLICATION TO IMPROVE WRITING ABILITY IN ENGLISH WRITING SKILL FOR NON ENGLISH DEPARTMENT STUDENTS - Sri Lestari (LET: Linguistics, Literature and English Teaching Journal, 2017)
Using padlet application has  function to encourage students to share and colaborate in writing and speaking. This study is aimed to know: teaching learning process in writing by using padlet application for Primary Education Department’s students, there is improvement of students writing English skill by using that application. Subject of this research was third semester students of Primary Education Department. This is Classroom Action. In collecting the data used some techniques: observed, interviewed, compiled the data in each cycle, and writing test. The data were analyzed by quantitative and qualitative. Result of this research were: those application can be implemented as online writing practices every time that made students ability improve, the situation of wall in padlet can stimulate students to explore idea because they could upload video, recording, or picture suitable with topic that can support their writing. Students improvement in writing can be seen from postest score in every cycles. Based on the results above, it can be concluded that implementing padlet application can improve students Non English Department’ writing skill